2001
DOI: 10.1128/jvi.75.17.7811-7817.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Leader Protein of Theiler's Virus Inhibits Immediate-Early Alpha/Beta Interferon Production

Abstract: Theiler's virus is a picornavirus responsible for a persistent infection of the central nervous system of the mouse, leading to a chronic demyelinating disease considered to be a model for multiple sclerosis. The leader (L) protein encoded by Theiler's virus is a 76-amino-acid-long peptide containing a zinc-binding motif. This motif is conserved in the L proteins of all cardioviruses, including encephalomyocarditis virus. The L protein of Theiler's virus was suggested to interfere with the alpha/beta interfero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
145
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(155 citation statements)
references
References 38 publications
(24 reference statements)
7
145
3
Order By: Relevance
“…Viruses and Cell Culture-Viruses used in this study were Theiler's virus DA1 and its L cys mutant, TM598, carrying two Cys to Arg mutations, disrupting the zinc finger of the L protein (29,30). The KJ6 and TM659 are the corresponding wild-type and L cys -mutant viruses carrying a capsid adapted to infect L929 cells (29,31).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Viruses and Cell Culture-Viruses used in this study were Theiler's virus DA1 and its L cys mutant, TM598, carrying two Cys to Arg mutations, disrupting the zinc finger of the L protein (29,30). The KJ6 and TM659 are the corresponding wild-type and L cys -mutant viruses carrying a capsid adapted to infect L929 cells (29,31).…”
Section: Methodsmentioning
confidence: 99%
“…The KJ6 and TM659 are the corresponding wild-type and L cys -mutant viruses carrying a capsid adapted to infect L929 cells (29,31). These viruses were produced as described previously by transfection of BHK-21 cells with viral RNAs transcribed in vitro from the corresponding infectious cDNA clones, pTMDA1, pTM598, pKJ6, and pTM659 (29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The L protein is produced by all members of the Cardiovirus genus and has been implicated in in vivo persistence because it modulates the host antiviral response (8,34,39). Although analysis revealed that the L protein is the second most divergent region across TMEV strains (Fig.…”
mentioning
confidence: 99%